A novel chick embryo model reveals endothelin receptor B is essential for collateral vessel development. (22nd September 2015) - Hoggar, EC; Pugh, SD; Wilson, S; Placzek, M; Crossman, DC; Chico, TJA
Abstract : Introduction: After arterial occlusion, collateral vessels develop by remodelling of endothelial communications between occluded and neighbouring arteries to restore blood flow. Collateral vessel formation is difficult to visualise in mammalian models in vivo. The extra-embryonic vasculature of the developing chick embryo is easily accessible and manipulated. We therefore established a novel model of collateral development in the chick, and used this to assess the contribution of endothelin receptor B (ETbR) to collateral formation. Method and Results: Right vitelline artery ligation was performed in 2.5 day-old chick embryos. After ligation embryos were observed every 4 h for 48 h and the extraembryonic vessels were photographed. The figure shows representative ligated and sham ligated embryos 24 h after ligation. Collateral vessels were observed arising from the unligated vitelline artery, crossing the midline to restore blood flow to the territory of the ligated vessel. Collateral vessels were quantified by number, diameter and total cross-sectional area of all collaterals (as a surrogate of flow-carrying capacity). Collateral vessels were first observed 4 h post-ligation, and increased in number to 8.6 ± 2.0 at 12 h post-ligation. By 48 h post-ligation the mean ± SEM collateral number fell to 3.6 ± 0.6. However, the diameter of collaterals steadily increased after ligation to 114.9 ± 13.4 μm by 48 h post-ligation. The total cross-sectional area of collaterals crossing the midline also steadily rose to 10.2 ± 2.3 × 10 3 μm 2 at 48 h (n  =  5). We next tested the effect of pharmacological inhibition of ETbR on normal embryonic vessels and collateral formation. 6 mm discs of filter paper were soaked in 5 μl of the ETbR antagonist BQ788 (5 μmol) or dimethylsulphoxide (DMSO). Discs were placed at various positions on the extraembryonic vessels, in ligated or unligated embryos, and the effect on the vessel beneath was assessed as above. When BQ788 was applied for 24 h to the vitelline artery of unligated embryos, this had no effect on vessel diameter (DMSO, 192 ± 200 μm, BQ788, 206 ± 220 μm, n  =  7 per group, p = ns). However, when BQ788 was applied to the site of collateral formation at the time of vitelline artery ligation (asterisk on fig ), this significantly reduced the collateral number at 24 h (DMSO, 3 ± 0.5; BQ788, 0.9 ± 0.3; n  =  8, p<0.01) and diameter (DMSO, 76 ± 6 μm; BQ788 16 ± 4 μm; n  =  18, p<0.01.) Conclusion: After vitelline arterial ligation in chick embryos, blood flow to the occluded territory is restored by collateral vessels between the ligated and unligated territories. Arterial ligation is followed by a rapid rise in the number of detectible collateral vessels, declining after 12 h post-ligation. The diameter of persisting collaterals and their flow-carrying capacity steadily increases over 48 h. Although ETbR inhibition has no effect on normal vasculature, it significantly inhibits the ability to form collateral vessels. This suggests that ETbR is required for collateral formation in response to arterial occlusion.